Morbidity and mortality in the antiphospholipid syndrome during a 10-year period: a multicentre prospective study of 1000 patients. Issue 6 (24th January 2014) - Cervera, R; Serrano, R; Pons-Estel, G J; Ceberio-Hualde, L; Shoenfeld, Y; de Ramón, E; Buonaiuto, V; Jacobsen, S; Zeher, M M; Tarr, T; Tincani, A; Taglietti, M; et al.
Abstract : Objectives: To assess the prevalence of the main causes of morbi-mortality in the antiphospholipid syndrome (APS) during a 10-year-follow-up period and to compare the frequency of early manifestations with those that appeared later. Methods: In 1999, we started an observational study of 1000 APS patients from 13 European countries. All had medical histories documented when entered into the study and were followed prospectively during the ensuing 10 years. Results: 53.1% of the patients had primary APS, 36.2% had APS associated with systemic lupus erythematosus and 10.7% APS associated with other diseases. Thrombotic events appeared in 166 (16.6%) patients during the first 5-year period and in 115 (14.4%) during the second 5-year period. The most common events were strokes, transient ischaemic attacks, deep vein thromboses and pulmonary embolism. 127 (15.5%) women became pregnant (188 pregnancies) and 72.9% of pregnancies succeeded in having one or more live births. The most common obstetric complication was early pregnancy loss (16.5% of the pregnancies). Intrauterine growth restriction (26.3% of the total live births) and prematurity (48.2%) were the most frequent fetal morbidities. 93 (9.3%) patients died and the most frequent causes of death were severe thrombosis (36.5%) and infections (26.9%). Nine (0.9%) cases of catastrophic APS occurred and 5 (55.6%) of them died. The survival probability at 10 years was 90.7%. Conclusions: Patients with APS still develop significant morbidity and mortality despite current treatment. It is imperative to increase the efforts in determining optimal prognostic markers and therapeutic measures to prevent these complications.